Surgical management of chronic pancreatitis: a single centre experience - Bhandari, Ramesh Singh; Kafle, Brindeswari; Lakhey, Paleswan Joshi; Singh, Keshav Prasad (Journal of Chitwan Medical College, 2017)
Abstract available on the PDF.